Measuring what matters: Evaluating the validity and reliability of teachers’ competency scales in China - Zhong, Min; Yusof, Mat Rahimi Bin (Edelweiss Applied Science and Technology, 2025)
This study aims to assess the validity and reliability of teacher competency scales in China, focusing on the Chongqing region. Adopting a cross-sectional survey design, the study utilizes Hay McBer’s teacher-teaching competency model to evaluate three key domains: Value of Teacher Professionalism (VTP), Teaching and Learning Skills (TLS), and Classroom Climate (CC). A sample of 200 teachers was surveyed, and data were analyzed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) through IBM SPSS and SEM AMOS programs. The methodology involved developing and validating a questionnaire based on expert consultations regarding face validity and content reliability (Cronbach’s alpha). The findings reveal high reliability and validity across all dimensions, supported by strong expert consensus. EFA indicated that the first three components explained 87.944% of the total variance, with the primary component accounting for 80.552%. CFA confirmed the constructs’ validity and reliability, with high loading factors, AVE, and CR values. The model fit indices suggested an adequate fit, with RMSEA within the acceptable range and strong incremental fit indices. This study provides a reliable and valid framework for assessing teacher competency in China, with practical implications for educational policy and teacher training programs.